Pengenalan dan Pelatihan Sistem Pengarsipan Elektronik di Kantor Kelurahan Limbungan Kecamatan Rumbai Timur Kota Pekanbaru - Rismayeti; Eko Noprianto (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
This service activity aims to provide understanding and training to Administrative Employees of Limbungan Village Office. A common problem with partners is that they do not have adequate skills in managing archives electronically. This service activity can improve the understanding and skills of the Administration employees in Limbungan Village Office. The outputs produced according to this activity plan are in the form of scientific articles. The method of implementing the activity is counseling. Submission of material is carried out by lecturers who are members of the team proposing community service activities. Based on the results of the pretest and posttest, it can be concluded that there is an increase in the participants' understanding of electronic archives and their management using a system, where this system will also assist in the retrieval of these archives.